Pediatric Intensive Care Unit Resident Educational Curriculum - Uchechi Oddiri; Grace Chong (Association of American Medical Colleges, 2020)
Introduction Consistent medical knowledge acquisition while caring for the critically ill can be challenging for learners and educators in the pediatric intensive care unit (PICU), a unit often distinguished by fluctuating acuity and severity. We implemented a standardized didactic curriculum for PICU residents to facilitate their acquisition and retention of knowledge in core PICU topics. Methods We developed a comprehensive standardized curriculum for PGY 2-PGY 4 PICU pediatric and internal medicine-pediatric residents. Thirteen core topics were administered as 30-minute didactic sessions during the rotation, using either PowerPoint slides or a dry-erase board. Residents were tested to assess knowledge acquisition and retention. Results Seventy-eight residents participated, 86% of whom completed posttests. Seventeen percent completed follow-up tests. Of the learners who participated, 60 (77%) completed pretests and posttests, indicating their confidence level each time. The pretest mean was 55% (SD = 14.4%), and the posttest mean was 64% (SD = 15.6%). This 9% increase was statistically significant (p = .001; CI, 3.9% to 14.8%). The follow-up test at 3 months, completed by 15% of this subgroup, demonstrated a mean score of 62% (SD = 14.5%). When matched with posttest scores (mean score of 64%, SD = 13.3%), there was no significant difference (p = .7398; CI, −11.7% to 16.2%), suggesting retention of previously acquired knowledge. Discussion Our standardized didactic curriculum effectively facilitated the acquisition and retention of the medical knowledge of core PICU topics among PICU residents, in addition to their usual experiential learning.